2021
DOI: 10.46300/9106.2021.15.178
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Technique to Generate Bounded Solutions for the Multidimensional Knapsack Problem: a Guide for OR Practitioners

Abstract: The 0-1 Multidimensional Knapsack Problem (MKP) is a NP-Hard problem that has important applications in business and industry. Approximate solution approaches for the MKP in the literature typically provide no guarantee on how close generated solutions are to the optimum. This article demonstrates how general-purpose integer programming software (Gurobi) is iteratively used to generate solutions for the 270 MKP test problems in Beasley’s OR-Library such that, on average, the solutions are guaranteed to be with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…More benefits of SSIT are detailed in [19]. Successful applications of SSIT to solve several binary integer programs (BIP) have been documented in the literature [14][15][16][17][18][19]. For these applications, SSIT typically generates solutions guaranteed to be within 0.1% of the optimums in about 60 seconds on standard PCs.…”
Section: Methodsmentioning
confidence: 99%
“…More benefits of SSIT are detailed in [19]. Successful applications of SSIT to solve several binary integer programs (BIP) have been documented in the literature [14][15][16][17][18][19]. For these applications, SSIT typically generates solutions guaranteed to be within 0.1% of the optimums in about 60 seconds on standard PCs.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses demonstrated that these SSIT results were as good as the best published results obtained from algorithms specifically designed to solve SKCPs. Also, using Gurobi, Lu et al (2021) employed the SSIT methodology to quickly (average of 88 seconds on a standard PC) generate solutions guaranteed to be, on average, within 0.09% of the optimum on 270 MKP instances commonly used in the literature. These results are far better than other published metaheuristic results for the MKP.…”
Section: Multiple Pass Mode (Ssit Methodology)mentioning
confidence: 99%
“…Also, using Gurobi, Lu et al. (2021) employed the SSIT methodology to quickly (average of 88 seconds on a standard PC) generate solutions guaranteed to be, on average, within 0.09% of the optimum on 270 MKP instances commonly used in the literature. These results are far better than other published metaheuristic results for the MKP.…”
Section: Overview Of the Simple Strategies For Solving Mmkps With Gurobimentioning
confidence: 99%
“…In this article a methodology first discussed in McNally [10] referred to as the simple sequential increasing tolerance (SSIT) matheuristic is used to quickly solve 135 SKCPs commonly used in the literature and 65 SVKCPs introduced in this article. Lu, et al [11] used SSIT to quickly (average of 88 seconds on a standard PC) generate solutions guaranteed to be close (average within 0.094% of the optimums) on 270 multidimensional knapsack problem (MKP) instances commonly used in the literature. These results are far better than other published metaheuristic results for the MKP.…”
Section: Introductionmentioning
confidence: 99%